Flexible and miniaturized power divider. Issue 3 (23rd March 2015) - Burdin, François; Podevin, Florence; Ferrari, Philippe
Abstract : A new flexible and miniaturized power divider (PD), based on the Wilkinson PD topology, is carried out in this paper. Flexibility and size reduction are achieved simultaneously thanks to both an open-stub loading the input port and additional transmission lines (TLines) connecting the output ports to the isolation resistance. Design equations and rules are given. As a proof-of-concept, two PDs working at 2.45 GHz were fabricated and measured. Then, on the basis of the previous developments, a 1:4 power-dividing feeding network was realized. It highlights the high performance and flexibility of the proposed PD. Agreement between simulation and measurement results is very good, for PDs as well as for the feeding network, thus validating the proposed approach. This concept is straightforward to be applied at higher frequencies, in particular in the millimeter-wave range on CMOS technologies, where flexibility in the choice of the TLines characteristic impedances and size reduction are mandatory.